The Implementation of the Role Play Method in Improving Students' Speaking Skill at the Eighth Grade Of UPTD SMP Negeri 4 Gunungsitoli Selatan - Harefa, Princes Tamwest; Harefa, Afore Tahir; Zega, Riswan; Waruwu, Yaredi (Universitas Nurul Jadid, 2025)
This research aimed to investigate the implementation of the Role Play method in improving students’ speaking skills at the eighth grade of UPTD SMP Negeri 4 Gunungsitoli Selatan. The study was conducted through Classroom Action Research (CAR) consisting of two cycles, each involving planning, action, observation, and reflection. The speaking skill indicators evaluated included pronunciation, grammar, vocabulary, fluency, and comprehension. In Cycle I, most students did not meet the Minimum Competency Criteria (KKM) of 75%. Only two students (7.5%) achieved the “good” category, eight students (30%) were in the “sufficient” category, while seventeen students (63%) remained in the “poor” category. These results indicated that students faced difficulties in speaking due to limited practice, lack of confidence, and challenges in pronunciation. The researcher addressed these issues by providing targeted pronunciation practice and encouraging students to prepare more thoroughly. Significant improvement was observed in Cycle II. The Role Play method enhanced student engagement and reduced anxiety, resulting in better speaking performance. Five students (19%) reached the “very good” category, twenty-one students (75%) were categorized as “good,” and only two students (7.5%) remained in the “sufficient” level. These findings demonstrate that the implementation of the Role Play method effectively improved students’ speaking skills.